Legal Analysis Of Judges' Decisions On The Imposing Of Sanctions For Perpetrators Of The Criminal Act Of Murder Study Of Decision NO. 264/PID.B/2024/PN RHL - Febri Kurniawan; Risdalina Risdalina; Indra Kumalasari M (CV. AFDIFAL MAJU BERKAH, 2025)
The method used in this research is normative legal research, namely research into problems by looking at the sources of applicable regulations relating to the title.Legal Analysis of Judge's Decision on the Imposition of Sanctions on Murder Perpetrators Study of Decision No. 264/PID.B/2024/PN RHL. InThe decision of the Rokan Hilir District Court No. 264/Pid.B/2024/PN Rhl has declared the Defendant Hari Kurniawan alias Ari bin Sugianto and has been proven legally and convincingly guilty of committing the crime of premeditated murder, as in the indictment of the Public Prosecutor by sentencing the Defendant to a prison sentence of 19 (nineteen) years.is very much in accordance with the concept of justice mentioned by John Rawls that the justice enforcement program with a people's dimension must pay attention to two principles of justice, namely: Providing equal rights and opportunities for the broadest basic freedoms as broad as the same freedom for everyone. The results of the study show that the judge in this decision based his considerations on Article 338 of the Criminal Code concerning ordinary murder, by adjusting the trial facts to the elements of the article. The judge's considerations involved subjective aspects, such as the defendant's psychological condition, and objective aspects, such as evidence and witness statements. Although the decision reflects elements of justice, several aspects, such as the application of maximum sanctions and efforts to prevent similar crimes, still require further evaluation. This study concludes that law enforcement in this case reflects the application of the principle of legality, but there is room for increased effectiveness through regulatory reform and more progressive implementation of criminal law.